A high-strength and toughness molybdenum alloy and preparation method thereof
By introducing nano BNNSs and MAX phase materials into the molybdenum alloy, a layered structure is formed, which solves the problem of insufficient brittleness and high-temperature strength of molybdenum alloy at room temperature, and achieves coordinated regulation of strength and toughness improvement at medium and low temperatures and strength and toughness at high temperatures.
Patent Information
- Application Number
- CN202310231469.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-03-13
AI Technical Summary
Molybdenum and its alloys are highly brittle at room temperature and have insufficient high-temperature strength, resulting in limited use of high-temperature structural materials.
By introducing nano BNNSs and MAX phase materials into molybdenum alloys, the layered structure of Mo/MAX/Mo/BNNSs is formed by using their non-phase-transformable and phase-transformable layered structures, which significantly enhances the strength and toughness of the alloy.
The strength and toughness of molybdenum alloys are significantly improved at medium and low temperatures, and the phase changeable characteristics of the MAX phase at high temperatures are regulated, solving the problem of the strong and toughness conflict between molybdenum alloys.
Smart Images

Figure GHA0000010268260000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material preparation, and specifically relates to a method for cooperatively regulating the high-temperature strength and toughness of a molybdenum alloy by using nano BN and MAX. Background Art
[0002] Molybdenum and its alloys have been widely used in many fields such as electronic and power equipment manufacturing, aerospace, defense industry, nuclear industry, etc. due to their high wear resistance, high electrical and thermal conductivity, high corrosion resistance, low thermal expansion coefficient and radiation swelling resistance. However, its room temperature brittleness and reduced high temperature strength restrict its industrial application as a high temperature structural material.
[0003] Existing technologies have carried out a lot of work on the problems of room temperature brittleness and reduced high temperature strength of molybdenum through alloying, and have made significant progress in regulating its strength and ductility at specific temperatures, especially significantly improving the processing performance of the material, and also playing a good auxiliary role in high temperature performance.
[0004] However, if molybdenum alloys are to have good processability, their solid solution and dispersed doping levels cannot be too high; if molybdenum alloys are to be used for a long period at high temperatures, they need more dispersed phases to pin dislocations and inhibit grain growth. Therefore, the inability to balance low- and medium-temperature processing performance with high-temperature service performance has become the main obstacle to the high-temperature application of molybdenum and its alloy materials. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and toughness molybdenum alloy and its preparation method, which can significantly enhance the strength and toughness of molybdenum alloy at medium and low temperatures, while utilizing the phase change characteristics of MAX phase at high temperatures to achieve coordinated regulation of medium and low temperature processing performance and high temperature strength and toughness of molybdenum alloy, based on improving the medium and low temperature processing characteristics and high temperature strength of molybdenum alloy.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] 1) Alloy powder preparation
[0008] First, 1-15% of MAX phase material Mo2TiAlC2 and 0.3-0.9% of BNNSs are taken by mass percentage, and the balance is pure molybdenum. Then, Mo, MAX phase material, Mo, and BNNSs are added to a ball mill in a stepwise cycle in the order of stepwise cycle. The ball milling is performed in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs. Then, the alloy powder is dried under vacuum.
[0009] 2) Pressing and sintering
[0010] The alloy powder is molded on a tablet press or a cold isostatic press at a pressing pressure of 180-240 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1800-1900°C for 8-10 h to obtain an alloy product;
[0011] 3) Plastic processing and heat treatment
[0012] The alloy product is hot forged at 1300-1650℃, and multiple processes are performed in 20-30 minutes by adjusting the gap between the grinding tool or the rolling plate to make the final deformation of the alloy product 80-90%. Then the deformed sample is placed in a vacuum of 10 -3 Pa or less, heat treatment at 800-1000℃ for 40-60min.
[0013] The pure molybdenum is 2-5 μm.
[0014] The ball mill in step 1) is a high-energy ball mill with a rotation speed of 300 to 500 r / min, and the ball milling time is 4 to 10 hours.
[0015] The high-temperature strong and tough molybdenum alloy prepared by the above preparation method has a room temperature yield strength of 580-730MPa, a tensile strength of 830-980MPa, an elongation of 28-45%, a high temperature yield strength of 330-390MPa at 1200°C, and a high temperature tensile strength of 480-550MPa at 1200°C.
[0016] The present invention uses BNNSs as the reinforcing phase of Mo, and combines the toughening effect of the layered structure MAX phase and the strengthening effect of BNNSs, and effectively utilizes the layered distribution of BNNSs instead of random distribution. The layered distribution of MAX will cause cracks to bridge, deflect and branch during the expansion process. All of these improve its ability to resist crack expansion, so that it has higher toughness than pure Mo. At high temperatures, because the thermal stability of BNNSs can maintain the original state, and the instability of the MAX phase lattice tends to release A-site atoms, a transformation from a hexagonal lattice to a cubic lattice occurs at the same time to produce a carbide reinforcing phase, and the A-site atoms are dissolved in the molybdenum alloy matrix to further achieve the purpose of high-temperature strengthening, thereby solving the problem of the strong-toughness conflict of the molybdenum alloy.
[0017] The present invention adopts the above technical solution, which has the following beneficial effects:
[0018] 1. The high-energy ball milling process adopts a segmented cyclic addition method to achieve the preparation of uniform and fine microstructure and layered structure of Mo / MAX / Mo / BNNS.
[0019] 2. By combining the performance and structural advantages of BNNS and MAX phases as well as press sintering process control, plastic processing and heat treatment, a balance between high temperature strength and room temperature plasticity of molybdenum alloy is achieved.
[0020] 3. The method of regulating the strength and toughness of molybdenum of the present invention provides conditions for strengthening other alloys and can be applied to other refractory metals, such as W\Ta\Nb, etc. DETAILED DESCRIPTION
[0021] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0022] A high-strength and toughness molybdenum alloy and a preparation method thereof of the present invention comprises the following steps:
[0023] 1) Alloy powder preparation
[0024] First, 1-15% of MAX phase material Mo2TiAlC2 and 0.3-0.9% of BNNSs are taken by mass percentage, and the balance is pure molybdenum (2-5 μm), and then Mo, MAX phase material, Mo, BNNSs are added to a ball mill in a stepwise cycle in the order of segmentation, and ball milled in an Ar gas environment (rotating speed 300-500 r / min, ball milling time 4-10 h) to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs, and then dried under vacuum to obtain an alloy powder;
[0025] 2) Pressing and sintering
[0026] The alloy powder is molded on a tablet press or a cold isostatic press at a pressing pressure of 180-240 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1800-1900°C for 8-10 h to obtain an alloy product;
[0027] 3) Plastic processing and heat treatment
[0028] The alloy product is hot forged at 1300-1650℃, and multiple processes are performed in 20-30 minutes by adjusting the gap between the grinding tool or the rolling plate to make the final deformation of the alloy product 80-90%. Then the deformed sample is placed in a vacuum of 10 -3 Pa or less, heat treatment at 800-1000℃ for 40-60min.
[0029] The present invention is further illustrated by some embodiments below.
[0030] Embodiment 1:
[0031] 1) Alloy powder preparation
[0032] First, 5% of MAX phase material Mo2TiAlC2, 0.6% of BNNSs, and the balance of 2-5 μm pure molybdenum are taken by mass percentage, and then Mo, MAX phase material, Mo, BNNSs are added into a high-energy ball mill with a rotation speed of 300 r / min in a stepwise cycle in the order of Mo, MAX phase material, Mo, and BNNSs, and ball milled for 10 hours in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs, and then dried under vacuum to obtain an alloy powder;
[0033] 2) Pressing and sintering
[0034] The alloy powder is molded on a tablet press or a cold isostatic press under a pressing pressure of 180 MPa for a pressing time of ≤ 40 min, and then placed in a 95% Ar + 5% H2 sintering furnace and sintered at 1800° C. for 10 h to obtain an alloy product;
[0035] 3) Plastic processing and heat treatment
[0036] The alloy product was hot forged at 1300℃, and the gap between the grinding tool and the rolling plate was adjusted to perform multiple processing in 30 minutes, so that the final deformation of the alloy product was 80%, and then the deformed sample was placed in a vacuum of 10 -3 Pa below, heat treated at 800℃ for 60min.
[0037] Embodiment 2:
[0038] 1) Alloy powder preparation
[0039] First, 10% of MAX phase material Mo2TiAlC2, 0.5% of BNNSs, and the balance of 2-5 μm pure molybdenum are taken by mass percentage, and then Mo, MAX phase material, Mo, BNNSs are added into a high-energy ball mill with a rotation speed of 400 r / min in a stepwise cycle in the order of Mo, MAX phase material, Mo, and BNNSs, and ball milled for 7 hours in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs, and then dried under vacuum to obtain an alloy powder;
[0040] 2) Pressing and sintering
[0041] The alloy powder is molded on a tablet press or a cold isostatic press under a pressing pressure of 200 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1850° C. for 9 h to obtain an alloy product;
[0042] 3) Plastic processing and heat treatment
[0043] The alloy product was hot forged at 1500℃, and the gap between the grinding tool and the rolling plate was adjusted to perform multiple processing in 25 minutes, so that the final deformation of the alloy product was 86%. -3 Pa, heat treated at 900℃ for 50min.
[0044] Embodiment 3:
[0045] 1) Alloy powder preparation
[0046] First, 8% of MAX phase material Mo2TiAlC2, 0.7% of BNNSs, and the balance of 2-5 μm pure molybdenum are taken by mass percentage, and then Mo, MAX phase material, Mo, BNNSs are added into a high-energy ball mill with a rotation speed of 500 r / min in a segmented cycle in the order of Mo, MAX phase material, Mo, and BNNSs, and ball milled for 4 hours in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs, and then dried under vacuum to obtain an alloy powder;
[0047] 2) Pressing and sintering
[0048] The alloy powder is molded on a tablet press or a cold isostatic press at a pressing pressure of 220 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1880°C for 8 h to obtain an alloy product;
[0049] 3) Plastic processing and heat treatment
[0050] The alloy product was hot forged at 1650℃, and the gap between the grinding tool and the rolling plate was adjusted to perform multiple processing in 20 minutes, so that the final deformation of the alloy product was 90%, and then the deformed sample was placed in a vacuum of 10 -3 Pa below, heat treated at 1000℃ for 40min.
[0051] Embodiment 4:
[0052] 1) Alloy powder preparation
[0053] First, 3% of MAX phase material Mo2TiAlC2, 0.4% of BNNSs, and the balance of 2-5 μm pure molybdenum are taken by mass percentage, and then Mo, MAX phase material, Mo, BNNSs are added to a high-energy ball mill with a rotation speed of 300 r / min in a segmented cycle in the order of Mo, MAX phase material, Mo, and BNNSs, and ball milled for 9 hours in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs, and then dried under vacuum to obtain an alloy powder;
[0054] 2) Pressing and sintering
[0055] The alloy powder is molded on a tablet press or a cold isostatic press at a pressing pressure of 190 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1830° C. for 10 h to obtain an alloy product;
[0056] 3) Plastic processing and heat treatment
[0057] The alloy product was hot forged at 1400℃, and the gap between the grinding tool and the rolling plate was adjusted to perform multiple processing in 28 minutes, so that the final deformation of the alloy product was 88%. Then the deformed sample was placed in a vacuum of 10 -3 Pa, heat treated at 850℃ for 55min.
[0058] Embodiment 5:
[0059] 1) Alloy powder preparation
[0060] First, 1% of MAX phase material Mo2TiAlC2, 0.3% of BNNSs, and the balance of 2-5 μm pure molybdenum are taken by mass percentage, and then Mo, MAX phase material, Mo, BNNSs are added into a high-energy ball mill with a rotation speed of 500 r / min in a stepwise cycle in the order of Mo, MAX phase material, Mo, and BNNSs, and ball milled for 5 hours in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs, and then dried under vacuum to obtain an alloy powder;
[0061] 2) Pressing and sintering
[0062] The alloy powder is molded on a tablet press or a cold isostatic press under a pressing pressure of 230 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1900°C for 8 h to obtain an alloy product;
[0063] 3) Plastic processing and heat treatment
[0064] The alloy product was hot forged at 1600℃, and the gap between the grinding tool and the rolling plate was adjusted to perform multiple processing in 22 minutes, so that the final deformation of the alloy product was 82%. -3 Pa, heat treated at 950℃ for 45min.
[0065] Embodiment 6:
[0066] 1) Alloy powder preparation
[0067] First, 15% of MAX phase material Mo2TiAlC2, 0.9% of BNNSs, and the balance of 2-5 μm pure molybdenum are taken by mass percentage, and then Mo, MAX phase material, Mo, BNNSs are added into a high-energy ball mill with a rotation speed of 400 r / min in a stepwise cycle in the order of Mo, MAX phase material, Mo, and BNNSs, and ball milled for 8 hours in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs, and then dried under vacuum to obtain an alloy powder;
[0068] 2) Pressing and sintering
[0069] The alloy powder is molded on a tablet press or a cold isostatic press at a pressing pressure of 240 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1860° C. for 9 h to obtain an alloy product;
[0070] 3) Plastic processing and heat treatment
[0071] The alloy product was hot forged at 1550℃, and the gap between the grinding tool and the rolling plate was adjusted to perform multiple processing in 26 minutes, so that the final deformation of the alloy product was 85%, and then the deformed sample was placed in a vacuum of 10 -3 Pa below, heat treated at 1000℃ for 40min.
[0072] The following table compares the performance of the alloy products prepared in Examples 1-6. (The comparison sample is pure molybdenum)
[0073] Table 1: Performance comparison
[0074]
[0075] It can be seen from Table 1 that the use of BNNSs as the reinforcing phase of Mo, combined with the toughening and strengthening effect of the layered structure MAX phase and its layered distribution with BNNSs and Mo matrix, can effectively solve the problem of the strength-toughness conflict of molybdenum alloy. When different contents of BNNSs and MAX phase are added to the Mo matrix, the room temperature yield strength of the molybdenum alloy can reach 580-730MPa, which is about 50%-90% higher than that of pure molybdenum; the room temperature tensile strength can reach 830-980MPa, which is about 55%-84% higher; the elongation can reach 28-45%, which is about 53%-250% higher; the high temperature yield strength can reach 330-390MPa, which is about 3-5 times higher; the high temperature tensile strength can reach 480-550MPa, which is about 2-3 times higher. From these results, it can be concluded that the use of the reinforcing phase of BNNSs, combined with the toughening and strengthening effect of the layered structure MAX phase and its layered distribution with BNNSs and Mo matrix is an extremely effective method to solve the problem of the strength-toughness conflict of molybdenum alloy.
[0076] The following further supplements the details of the present invention:
[0077] On the basis of improving the low temperature processing characteristics and high temperature strength of molybdenum alloys, the present invention utilizes the combination of nano BNNSs "non-phase change layered structure" and MAX phase "phase changeable layered structure" materials as reinforcement phases, which significantly enhances the strength and toughness of molybdenum alloys at low temperature. At high temperature, the phase changeable characteristics of the MAX phase are utilized to regulate the ratio of second phase particle reinforcement and layered material reinforcement, thereby achieving coordinated regulation of the low temperature processing performance and high temperature strength and toughness of the molybdenum alloy.
[0078] To achieve the coordinated improvement of the mechanical properties of molybdenum alloys, it is necessary to solve both the room temperature brittleness problem and the high temperature strength problem, so as to achieve the balance between the strength and toughness of molybdenum alloys. The key points of the present invention are: first, according to the target performance requirements, BNNSs and MAX phase layered structure materials are selected as reinforcing phases; second, through the composition ratio and the target grain size requirements, high-energy ball milling is used to achieve the control of alloy powder particle size and mechanical alloying; third, effective pressing and sintering methods are used. During the sintering process, with the shrinkage of the powder particle size and the elimination of the gaps between adjacent powders, as well as the further densification of the Mo / BNNS / MAX alloy, the preparation of a molybdenum alloy with fine and uniform structure is achieved. Fourth, the sintered samples are subjected to plastic processing and heat treatment to achieve the balance between the strength and toughness of the molybdenum alloy.
[0079] First, BNNSs and MAX phase layered structure materials are selected as reinforcement phases. The principle is similar to that of natural pearls. The pearl layer is a natural composite material composed of a brittle mineral layer and a small amount of organic components. It is precisely because of the unique lamellar structure that it not only has high strength, but also has excellent toughness. It can resist external impact in the complex and changeable environment of nature and hinder the initiation and expansion of cracks. BNNSs is similar to the structure of graphene, with a large specific surface area and excellent mechanical properties, thermal stability, chemical stability, etc. It is an ideal reinforcement phase for preparing molybdenum alloy-based composite materials with excellent performance. MAX phase layered hexagonal crystals combine the advantages of metals and ceramics, have excellent electrical and thermal conductivity, good processing performance, and low sensitivity to thermal shock. At the same time, it has a high melting point, light weight, high hardness, high wear resistance, and oxidation resistance. Of course, the improvement of the mechanical properties of the molybdenum alloy material formed by Mo / BNNS / MAX is closely related to the contribution of the strengthening and toughening mechanism. Like other alloys, Mo / BNNS / MAX alloy involves multiple strengthening mechanisms, including fine grain strengthening, dislocation strengthening, Orowan strengthening and load transfer strengthening. The first two are closely related to the content of strengthening and toughening phase. With the increase of content, on the one hand, the pinning effect becomes more prominent, further limiting the growth of matrix grains during sintering, and on the other hand, a higher dislocation density will be generated at the grain boundary, leading to more significant dislocation strengthening; while the latter two are closely related to interface bonding. Only when the interface bonding is strong enough can the hindering effect of relative dislocation slip and the load bearing capacity of the strengthening be fully exerted.
[0080] Second, high-energy ball milling is used to control the particle size of alloy powders and mechanical alloying. To achieve the compactness and uniformity of the sintered samples, certain powder size requirements and the uniformity and alloying degree of the alloy powders are necessary. At the same time, according to the performance requirements, the layered structure characteristics of BNNSs and MAX phases need to be used to construct the layered structure of Mo / MAX / Mo / BNNS. Therefore, the composition ratio of Mo, MAX, Mo, and BNNSs is added to the high-energy ball mill in a segmented cycle. Through high-energy ball milling, the powders are repeatedly collided, deformed, cold welded, and broken between the grinding balls and between the grinding balls and the material tank, thereby realizing the complex physical and chemical process of alloying between elements, thereby preparing a layered structure with uniform and fine microstructure (up to submicron level) and Mo / MAX or Mo / BNNS, laying the foundation for the next sintering.
[0081] Third, effective pressing and sintering. Isostatic pressing + sintering is a commonly used powder metallurgy method with unique advantages. Isostatically pressed products have high density, generally 5 to 15 higher than unidirectional and bidirectional compression molding. The density of the green sheet is uniform. In compression molding, whether it is unidirectional or bidirectional pressing, uneven density distribution of the green sheet will occur. The isostatic fluid medium transmits pressure, which is equal in all directions. The compression of the sheath and the powder is roughly the same, and there is no relative movement between the powder and the sheath. There is little friction resistance between them, and the pressure only drops slightly. This density drop gradient is generally less than 1%. Therefore, the density of the green sheet can be considered to be uniform. Isostatically pressed products have excellent performance, short production cycle and wide application range. Therefore, the isostatic pressing + sintering technology is used to sinter the Mo, BNNSs and MAX phase powders after high-energy ball milling to prepare layered molybdenum alloy samples.
[0082] Fourth, plastic processing and heat treatment. Usually, the billet rolling temperature of pure molybdenum alloy and molybdenum alloy should be close to or higher than its recrystallization temperature. The heating temperature of molybdenum hot rolling is generally 1300-1650℃, and the warm rolling is generally 800-1000℃. When low-temperature rolling is carried out at a lower temperature, the deformation resistance is large and internal microcracks are easily generated, so multiple stress relief annealing is required. The rolling temperature, deformation amount, and pass deformation rate will have a great impact on the quality of the rolled product. After large deformation, the strength of the alloy increases and the plastic toughness decreases, so heat treatment at different temperatures is required to optimize the alloy structure and obtain molybdenum alloy products with good strength and toughness matching.
Claims
1. A method for preparing a high-strength and toughness molybdenum alloy, characterized in that: 1) Alloy powder preparation First, 1-15% of MAX phase material Mo2TiAlC2 and 0.3-0.9% of BNNSs are taken by mass percentage, and the balance is pure molybdenum. Then, Mo, MAX phase material, Mo, and BNNSs are added to a ball mill in a stepwise cycle in the order of stepwise cycle. The ball milling is performed in an Ar gas environment to obtain a uniform and fine submicron microstructure and a layered structure of Mo / MAX / Mo / BNNSs. Then, the alloy powder is dried under vacuum. 2) Pressing and sintering The alloy powder is molded on a tablet press or a cold isostatic press at a pressing pressure of 180-240 MPa for a pressing time of ≤40 min, and then placed in a 95% Ar+5% H2 sintering furnace and sintered at 1800-1900°C for 8-10 h to obtain an alloy product; 3) Plastic processing and heat treatment The alloy product is hot forged at 1300-1650℃, and multiple passes are performed in 20-30 minutes by adjusting the gap between the grinding tool or the rolling plate to make the final deformation of the alloy product 80-90%. Then the deformed sample is placed in a vacuum of 10 -3 Pa or less, heat treatment at 800-1000℃ for 40-60min.
2. The method for preparing a high-strength and toughness molybdenum alloy according to claim 1, characterized in that: The pure molybdenum is 2-5 μm.
3. The method for preparing a high-strength and toughness molybdenum alloy according to claim 1, characterized in that: The ball mill in step 1) is a high-energy ball mill with a rotation speed of 300 to 500 r / min, and the ball milling time is 4 to 10 hours.
4. A high temperature strong and tough molybdenum alloy prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The molybdenum alloy has a room temperature yield strength of 580-730 MPa, a tensile strength of 830-980 MPa, an elongation of 28-45%, a high temperature yield strength of 330-390 MPa at 1200° C., and a high temperature tensile strength of 480-550 MPa at 1200° C.
Citation Information
Patent Citations
Aluminum-boron nitride nanosheet layered composite material and preparation method thereof
CN113355563A
Molybdenum alloy added with MAX phase and preparation method of molybdenum alloy
CN113862540A